New international economic order and systemic reforms - Bokil, S.V. (Bangalore, 1988)
The book begins with an analysis of the NIEO reform agenda. The "authors find that this is a middle of-the-road programme, and implies no design to destabilise the conservative thinkers in the North. Moreover, the programme does not contain any radical redistributive demands to dispossess the richer countries of their affluence. Even then the North-South dialogue has reached a stalemate due to unfounded fears and lack of bargaining leverage with the South. As a way out, the authors believe that focusing attention on systemic reforms may lay the basis for a new international economic order. A powerful case, based on mutual gains, is made for a set of systemic reforms in the areas of international liquidity, exchange rates, aid and credit flows, debt relief, and the IMF conditionality. Systemic reforms are possible if we grasp the principles behind international cooperation. The authors believe that India can play an active role if she modifies her negotiation strategies.
Keywords: International finance